Optimalisasi Pemilihan Lapangan Badminton: Integrasi Metode SAW dan AHP dalam Sistem Pendukung Keputusan - Lestariningsih, Endang; Nadila, Latifia; Handoko, Widiyanto Tri; Amin , Imam Husni Al (LPPM UNIKA Santo Thomas Medan, 2025)
Badminton is one of the most popular sports in the world, with Indonesia having achieved great success in international competitions. The high level of public interest in this sport requires the availability of adequate court facilities. However, the comfort of badminton court facilities still varies, so a decision support system is needed to help select the optimal court. This study develops a decision support system based on the integration of the Simple Additive Weighting (SAW) and Analytical Hierarchy Process (AHP) methods. SAW is used for criterion weighting, while AHP is applied in the ranking stage of alternatives. This combination of methods was chosen due to its ability to process qualitative data from player and athlete evaluations, as well as quantitative court data, while addressing complex issues through hierarchy-based prioritisation. The results of the study indicate that the system is capable of consistently weighting criteria (CR < 0.1). This study also produced a ranking of badminton courts in North Brebes based on seven criteria (price, floor type, lighting, bathrooms, scoreboards, cooperatives, and parking lots) and identified priority facilities. Court 33 in Brebes was selected as the best alternative with a preference value of 0.7485.